2012
DOI: 10.1002/pmj.21280
|View full text |Cite
|
Sign up to set email alerts
|

Governance of Public Investment Projects in Ethiopia

Abstract: The purpose of this article is to map and review the governance of public investment projects in Ethiopia and to identify the most important front-end challenges of public investment projects in the country. The research focuses on the front-end governance of major construction projects. The findings of the research indicate that the top-down project approach, lack of mandatory control gateways at the front-end project preparation and decision-making stages, and weak links between project stakeholders affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 3 publications
0
37
0
Order By: Relevance
“…When public investment projects are being planned, the task of designing and defining project goals based on the development strategy of the country has not been given sufficient attention. Objectives have been set based on the interests of project initiators, usually decision makers (Shiferaw & Klakegg, 2011). Several projects have no definite objectives.…”
Section: Projects In Developing Countriesmentioning
confidence: 99%
“…When public investment projects are being planned, the task of designing and defining project goals based on the development strategy of the country has not been given sufficient attention. Objectives have been set based on the interests of project initiators, usually decision makers (Shiferaw & Klakegg, 2011). Several projects have no definite objectives.…”
Section: Projects In Developing Countriesmentioning
confidence: 99%
“…A lack of local knowledge may increase the risk of using technical or organizational processes or models that are not compatible with local conditions (Wall 1993;Ofori 1994;Bakuli 1994;Sohail et al 2004;Shiferaw et al 2012). Furthermore, studies have highlighted challenges from the lack of common objectives amongst different stakeholders that have different missions and agendas (FHWA 2007;Lizarralde et al 2013) or from a lack of trust between the different stakeholders, which hampers the implementation of the asset management system (Ika et al 2012).…”
Section: Literature Review On Potential Asset Management Barriersmentioning
confidence: 99%
“…This implies that top management has to support the implementation, provide resources (Mizusawa and McNeil 2006), ensure clarity in expectations, scope and job descriptions (Arts and Van Lamoen 2005;Atkinson et al 2006;PMI 2013;Ziara et al 2002;Shiferaw et al 2012), and ensure that communication channels exist between departments (Vanier 2001;FHWA 2007;Hawkins and Smadi 2013). Management also needs to establish and ensure that monitoring procedures, criteria, and standards are available and used (McNeil et al 2000;Moon et al 2009;Arif and Bayraktar 2012;Mizusawa and McNeil 2006).…”
Section: Literature Review On Potential Asset Management Barriersmentioning
confidence: 99%
“…A major challenge is related to how the evaluation and selection process, which is part of the decision-making process, is designed to guide the decision maker through the process. Research by Shiferaw et al (2012) indicates that the process of selecting public investment projects in developing countries is often unstructured and inconsistent, and that, in most cases, there appears to be no system in place to identify the public's current needs and demands in order to prioritise projects. In these countries, the ultimate decision often ignores society's priorities and is identified without any clear degree of project prioritisation.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Empirical studies have indicated that public investment projects in Thailand are typically proposed and selected based on strategic objectives that are not necessarily linked to the needs of local communities. Scientific evidence also shows that the decisions made at the national level do not correspond with the priorities of local communities, but are based instead on the priority of high-level perspectives (Besley & Coate, 2003), (Shiferaw et al, 2012). The process used is a fundamentally centralised, top-down approach in which decisions are made by a central government, based on the notion that investing large sums of money in large-scale projects will bring more economic progress to the country (Besley & Coate, 2003).…”
Section: Problem Descriptionmentioning
confidence: 99%